Analisis Risiko Bahaya Kesehatan dan Keselamatan kerja (K3) Pengelasan dengan Metode Fishbone Diagram dan Job Safety Analisis (JSA) - Cahyono, Manggi Dwi; Susiati, Devi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Occupational Safety and Health (K3) are activities that ensure the creation of safe working conditions, avoiding physical and mental disorders. The aim of this research is to determine the risk of severity of welding workers who do not use Personal Protective Equipment (PPE). This research uses 2 methods, the fishbone diagram method and job safety analysis. The survey technique was carried out by taking a sample of 15 welding worker respondents in the company. The results of this research are that welding workers experience a very high level of risk to Occupational Health and Safety due to the lack of Personal Protective Equipment (PPE) used. So companies must provide, comply with and prioritize (K3) welding. The company must also facilitate and require all workers to use safety equipment such as welding Personal Protective Equipment (PPE) that meets the Indonesian National Standard (SNI).